2004
DOI: 10.1002/eat.10250
|View full text |Cite
|
Sign up to set email alerts
|

Looking good—family focus on appearance and the risk for eating disorders

Abstract: Findings support the view that family risk factors have a more potent influence on young women who are easily made anxious-perhaps because they are more sensitive to, or more likely to internalize, pressures and expectations to conform to family values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 37 publications
4
16
0
3
Order By: Relevance
“…We conclude that specific cognitive and behavioural dimensions of ED in both parents can influence the development of some forms of ED in early adolescence. Our data support the data provided by other authors [7,15] which indicate that parents may play in role in their children attaching greater importance to their physical appearance and thinness-and, therefore, in the prevalence of ED.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We conclude that specific cognitive and behavioural dimensions of ED in both parents can influence the development of some forms of ED in early adolescence. Our data support the data provided by other authors [7,15] which indicate that parents may play in role in their children attaching greater importance to their physical appearance and thinness-and, therefore, in the prevalence of ED.…”
Section: Discussionsupporting
confidence: 91%
“…Benninghoven et al [3] showed that an alternative viewpoint is that the family can transmit issues that are more directly related to eating pathology such as weight, shape, and eating behaviour. Perceived weight-related pressure [34] and the importance of physical appearance for the family [7,15] seem to influence the development of disordered eating patterns. Parental social values that emphasize physical attractiveness, admire thinness and encourage behaviours such as dieting and exercise in the pursuit of an ideal body shape may contribute to eating problems in their children [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested for example that, among girls, proneness to anxiety may increase vulnerability to family influences (Davis et al 2004). It is not unlikely that other individual characteristics may play a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Davis, Shuster, Blackmore, and Fox (2005), investigated 'proneness to anxiety' as a moderating variable of family orientation towards appearance and disordered eating. Their results revealed that participants who claimed to be easily made anxious, showed more vulnerability to family influences.…”
Section: Mediating Variablesmentioning
confidence: 99%